Stress Control Method Applied to Stabilization of Underground Coal Mine Openings (e5cbe8ad-30a8-4144-a7b5-db19e81a247a) - Shosei Serata (International Conference on Ground Control in Mining, 1984)
Serious floor heave of up to 2.4 m in a 2.4-m high mine entry was eliminated by applying the stress control method of mining, as a last resort, at the No. 5 coal mine of Jim Walter Resources, Inc., in the Black Warrior coal basin near Birmingham. Alabama. Underground observation of the first 3-room entry created using the stress control method is discussed here. The behavior of the test entry, which eliminated the heave problem, is analyzed in relation to similar studies conducted in a salt mine under similar ground conditions by utilizing finite element analysis.